Islamic rationalism: a critical evaluation of Harun Nasution's thought - Ishak, Mohd. Shuhaimi (IIUM Press, 2009)
Harun Nasution is an important name in the reformation of religious thought in Indonesia. His idea of reformation in religious thought of Harun Nasution is by introducing a new theology known as Islamic rationalism modelled along the lines of the classical rational thought of Mu'tazilah. His approach via education had to a certain extent exerted considerable influence on the development of contemporary religious thought particularly at IAINs (Institute Agama Islam Negeri or State Islamic Religious Institute). This book examined the theology of Islamic rationalism promoted by Harun Nasution, as the only means to change the attitude of Muslims. Harun Nasution believes that the cause of the backwardness of Muslims is theological in nature and thus can be resolved by the introduction of a new theology called Islamic rationalism. Harun Nasution’s rationalism focuses on the relationship of human reason to human action, that is, while God gives the capacity, man has the free will to determine the shapes and forms of actions. A new system of values under a new theology in Islam is needed to enable Muslims to understand and interpret their environment and act accordingly. The book also examines the impact of Harun Nasution's Islamic rationalism in religious education at IAIN and the great influence theology had so far exerted in the development of intellectual and religious thoughts at IAIN in Indonesia.